2017
DOI: 10.5861/ijrsp.2017.2000
|View full text |Cite
|
Sign up to set email alerts
|

Big five personality factors and emotional intelligence among university students: A gender perspective

Abstract: Students are the assets of a country. Personality traits and emotional intelligence are two important factors in study setting and also in career. Purpose of the study was to investigate the gender differences on big five personality traits and emotional intelligence of the university students. The data were collected from different institutes of Lahore, Pakistan.Sample size consists of (300) students in which 150 were male participants and 150 were female participants. Two questionnaires were administered, Wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…However, in a study on postgraduate students, Joshi and Thingujam (2009) reported inadequate alpha reliability values for the NEO-FFI. The obtained psychometric values of the FFM measures are not mentioned in the other studies including 12 studies which administered the NEO-FFI/NEO-PI-R on college students or working youth of 18–30 years of age (Chaturvedula and Joseph, 2007; Pavitra et al, 2007; Sharma et al, 2010; Fazeli, 2012; Sushma et al, 2015; Sharma and Gill, 2016; Srivastava and Mishra, 2016; Gupta, 2017; Mandal, 2017; Rita, 2017; Ullah, 2017; Abbas and Khan, 2018). Singh and Ullah (2016) used NEO-PI-R with adolescent school students, but did not mention the obtained alpha reliability values.…”
Section: Introductionmentioning
confidence: 97%
“…However, in a study on postgraduate students, Joshi and Thingujam (2009) reported inadequate alpha reliability values for the NEO-FFI. The obtained psychometric values of the FFM measures are not mentioned in the other studies including 12 studies which administered the NEO-FFI/NEO-PI-R on college students or working youth of 18–30 years of age (Chaturvedula and Joseph, 2007; Pavitra et al, 2007; Sharma et al, 2010; Fazeli, 2012; Sushma et al, 2015; Sharma and Gill, 2016; Srivastava and Mishra, 2016; Gupta, 2017; Mandal, 2017; Rita, 2017; Ullah, 2017; Abbas and Khan, 2018). Singh and Ullah (2016) used NEO-PI-R with adolescent school students, but did not mention the obtained alpha reliability values.…”
Section: Introductionmentioning
confidence: 97%
“…23,24 The psychometric qualities of the NEO-PI-R, NEO-FFI, and the NEO-FFI-3 have presented a robust verification base in the Western societies 2,8,20,21,26,30,31 and many cross-cultural studies including different cultures in the world. 13,[15][16][17]19,22,23,25,[27][28][29] The replication of the structure of NEO Inventories in Indo and non-Indo European languages provides strong evidence of their universality. Unfortunately, the researchers did not find any Arabic adaptation of the psychometric measures of the NEO-FFI -3 Inventory.…”
Section: Introductionmentioning
confidence: 99%